Synthesis of Ni(Co)/Pd Ternary Nanostructures and Their Catalytic Activity in p–Nitrophenol Reduction Processes - Bazylyak, Liliya; Lyutyy, Pavlo; Vynar, Vasyl; Shepida, Mariana; Kuntyi, Orest; Kytsya, Andriy (Indonesian Journal of Chemical Research, 2024)
Ni(Co)/Pd nanosized ternary composite materials have been synthesized by the galvanic replacement method. The structure and phase composition of the obtained Ni(Co)/Pd nanostructures were investigated using SEM, EDX and X–ray powder diffraction. The catalytic activity of the synthesized polymetallic Ni(Co)/Pd nanoparticles was studied using the example of the reduction reaction of p–nitrophenol with NaBH4 solution. It was found that in all cases the process of reduction of p–nitrophenol NaBH4 in the presence of Ni(Co)/Pd nanoparticles as a catalyst is described by the first-order kinetic equation for p–nitrophenol. The catalytic activity of the studied nanoparticles based on nickel (Ni) is varied in the following order: Ni < Ni(Co) < Ni(Pd) < Ni(Co)/Pd. It was shown that the decoration of nanoparticles based on d–elements (Ni, Co) with palladium (Pd) significantly increases of their catalytic activity. Moreover, the reduction rate of p–nitrophenol in the presence of Ni(Co)/Pd is almost three times higher, compared to effective catalytic systems known from the references, i. e., such nanosystems can be considered as promising material for the development of new types of magnetically separable catalysts for the production of aminoaromatic compounds.